Population And Digital Economy: A View from Russia - 1Boris B. PODGORNY; Natalia V. VOLOKHOVA; Mariya V. OBOZNAYA; Albina Yu. OGURTSOVA (Communications of International Proceedings, 2021)
The current situation both in the country and in the world states impetuous digitalization in every sphere of life. When analyzing the project “Digital economy of the Russian Federation”, it becomes quite obvious that economic details do not play a dominative role. Therefore, the purpose of the project is to drastically change the society due to the amendment of the political and the social structure.  Factually, the process of utter digitalization affects the whole population of the country, what leads to substantial change of habitual structure of society and defines the necessity for the community to understand and accept such rapid changes, the readiness of the society to implement the purposes of the project. This research is aimed at exploring the level of digital literacy of the community and its competence when using digital technologies, revealing advantages and disadvantages of implanting the main positions of digital economy into social environment, defining levels of protection of personal information in digital environment and estimating the media-competence of the society.
Keywords: Digital Economy; Population; Digital Literacy.